Bhikkhu Vivekanand; Vipassyana Meditataion and his address as a guest of honour to the 8the SSARC Psychiatric Federation International Conference in Lumbini Nepal - Upadhyaya, K D (Journal of Psychiatrists’ Association of Nepal, 2015)
N/A J Psychiatric Association of Nepal Vol .3, No.2, 2014, pp: 53-54 DOI: http://dx.doi.org/10.3126/jpan.v3i2.12400